Uno Antioxidant capacity and antimicrobial activity of loquat (Eriobotrya japonica) extracts from Tenango del Valle, State of Mexico - JUVENTINO-GIL, Brenda Angelica; IBÁÑEZ, Ana Tarin Gutiérrez IBÁÑEZ; JESÚS, Rosa Laura Ocaña de; VILLANUEVA-CARVAJAL, Adriana; GARCÍA-SAUCEDO, Pedro Antonio; SICLÁN, Martha Lidya Salgado; MARTÍNEZ, Luz Raquel Bernal; CAMPUZANO, Gaspar Estrada; LARA, Isis Kendra Sánchez (Food Science and Technology, 2024)
Nationwide, the State of Mexico is the leading producer of loquat (Eriobotrya japonica); however, there are no records about the antioxidant and antimicrobial properties of such fruits from this place. The objective of this research was the evaluation of extracts of different loquat morphological structures (pulp with epidermis, leaves, and seeds) in ethanolic and hydromethanolic solvents. Four methods were used to evaluate the antioxidant capacity: 2,2-Diphenyl-1-Picrylhydrazyl (DPPH), N,N-Dimethyl-p-phenylenediamine Dihydrochloride (DMPD), Folin–Ciocalteu, and ferric-reducing antioxidant power (FRAP). Antimicrobial activity was determined using disk diffusion assays applied to two bacterial strains, Escherichia coli and Salmonella Typhimurium, and two phytopathogenic fungi strains, Fusarium oxysporum and Rhizoctonia solani. An analysis of variance and Tukey’s test at 5% were performed. There were significant differences between the plant material and the solvent used (p < 0.05). The results showed that the ethanol pulp extract presented the highest antioxidant capacity by the DPPH method; in DMPD, the ethanol leaf extract indicated high values of Trolox equivalents and presented the highest values for FRAP, and hydromethanol pulp also had high antioxidant activity; finally, for the Folin–Ciocalteu method, highest values were obtained from the seed extracts with both solvents. The extracts obtained from the pulp with ethanol and hydromethanol showed antibacterial capacity against E. coli and S. typhimurium. Antifungal activity was only present only in the pulp extract obtained with hydromethanol.